
(1/11+1/21+1/31+1/41)*(1/21+1/31+1/41+1/51)-(1/11+1/21+1/31+1/41+1/51)*(1/21+1/31+1/41)
展开全部
解:
令a=1/11+1/21+1/31+1/41+1/51
则(a-1/51)(a-1/11)-a(a-1/11-1/51)
=a²-(1/11+1/51)a+1/51×1/11-a²+(1/11+1/51)a
=1/11×1/51
=1/561
令a=1/11+1/21+1/31+1/41+1/51
则(a-1/51)(a-1/11)-a(a-1/11-1/51)
=a²-(1/11+1/51)a+1/51×1/11-a²+(1/11+1/51)a
=1/11×1/51
=1/561
展开全部
令1/11+1/21+1/31+1/41=a
1/21+1/31+1/41+1/51=b
原式=ab-(a+1/51)(b-1/51)=(a-b)1/51+1/51^2=(1/11-1/51)1/51+1/51^2=1/(11*51)=1/561
1/21+1/31+1/41+1/51=b
原式=ab-(a+1/51)(b-1/51)=(a-b)1/51+1/51^2=(1/11-1/51)1/51+1/51^2=1/(11*51)=1/561
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
设x=1/11+1/21+1/31+1/41
y=1/21+1/31+1/41+1/51
(1/11+1/21+1/31+1/41)*(1/21+1/31+1/41+1/51)-(1/11+1/21+1/31+1/41+1/51)*(1/21+1/31+1/41)
=xy-(x+1/51)(y-1/51)
=xy-xy-1/51x+1/51y+1/51^2
=1/51(1/11-1/51)+1/51^2
=1/11×1/51
=1/561
y=1/21+1/31+1/41+1/51
(1/11+1/21+1/31+1/41)*(1/21+1/31+1/41+1/51)-(1/11+1/21+1/31+1/41+1/51)*(1/21+1/31+1/41)
=xy-(x+1/51)(y-1/51)
=xy-xy-1/51x+1/51y+1/51^2
=1/51(1/11-1/51)+1/51^2
=1/11×1/51
=1/561
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询